Preexisting cognitive impairment in intracerebral hemorrhage - Laible, Mona; Horstmann, Solveig; Möhlenbruch, Markus Alfred; Schüler, Svenja; Rizos, Timolaos; Veltkamp, Roland (Acta neurologica Scandinavica, 2017)
Objectives: Preexisting cognitive impairment is a predictor of cognitive decline after ischemic stroke, but evidence in intracerebral hemorrhage (ICH) is limited. We aimed to determine the prevalence of premorbid cognitive impairment in patients with ICH. Materials and Methods: We included patients with acute ICH. Pre-ICH cognitive impairment was determined based on the results of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) that uses information from close relatives. Patients were assessed as having been cognitively impaired with an IQCODE score of ≥3.44; an IQCODE ≥4.00 indicated pre-ICH dementia. CT and MRI images were reviewed to determine the extent of white matter lesions and to measure the radial width of the temporal horn as marker of brain atrophy. We investigated differences of cardiovascular risk factors and imaging data between patients with and without pre-ICH cognitive impairment using correlation analyses, uni- and multivariable regression models. Functional neurological state was assessed using the modified Rankin Scale (mRS). The mRS was dichotomized at the level of 3, and a premorbid mRS of 0-2 was considered as functional independency. Results Among the 89 participants, median age was 70 years (interquartile range 58-78) and 52 (58.4%) were male. IQCODE indicated pre-ICH cognitive impairment in 18.0% (16 of 89), and 83.1% were functionally independent before ICH. Cognitive impairment was associated with a premorbid mRS≥3 (chi squared test, P=0.009). In multivariable analysis, prior stroke/transient ischemic attack (OR 18.29, 95%-CI 1.945-172.033, P=.011) and hematoma volume (OR 0.90, 95%-CI 0.812-0.991, P=.033) were independently associated with pre-ICH cognitive impairment. Conclusions: In conclusion, cognitive impairment frequently precedes ICH. A higher frequency of cerebrovascular events suggests a role of vascular processes in the development of cognitive impairment before ICH.